Pregnancy or Psychological Outcomes of Psychotherapy Interventions for Infertility: A Meta-Analysis - Zhou, Rong (Front Psychol, 2021)
Background: The pregnancy and psychological status of infertile couples has always been a concern, but there is no clear evidence for the efficacy of psychotherapy for infertile couples. This study aimed to summarize the current evidence of the effects of psychotherapy on psychological and pregnancy outcomes for infertile couples. Method: We searched Ovid MEDLINE, Ovid EMbase, The Cochrane Library, and Web of Science (ISI) for articles published from 1946 to June 26, 2020. The pregnancy outcomes, psychological outcomes, and acceptability were involved in the study. Results: Overall, 29 studies with a combined total of 3,522 adult participants were included in the meta-analysis. Compared with a placebo, psychotherapy was associated with the pregnancy rate [risk ratio (RR) = 1.43, 95% CI [1.07, 1.93]], total psychological scales associated with infertility [standardized mean difference (SMD) = −0.33 95% CI [−0.63, −0.02]], subsymptoms of psychological scores using the 28-item version of GHQ (including social function [MD = −3.10, 95% CI [−4.30, −1.90]] and depression [MD = −3.90, 95% CI [−5.36, −2.44]], and depression [MD = 3.60, 95% CI [2.25, 4.95]] using the 14-item version of Hospital Anxiety and Depression Scale, but it had no statistically significant association with the other outcomes. In the stratified analyses, the pregnancy rate using assisted reproduction, cognitive behavioral therapy (CBT), and the integrative body–mind–spirit (BMS); total psychological scales associated with infertility using other treatments and more than a month; and anxiety using BMS had significant statistical significance. The funnel plots of all outcomes were approximately symmetrical, and no significant publication bias was found. Conclusions: The study showed that psychotherapy can lead to improvements in the pregnancy rate for infertile patients, especially for patients receiving assisted fertility. In addition, it may help improve total psychological scales associated with infertility and depression. CBT and BMS play an important role in improving rate of pregnancy, and BMS is associated with reducing anxiety. Although psychological interventions had limited effects on the pregnancy outcomes of infertility, our study still recommended that psychotherapies, in particular CBT and BMS, were applied to the therapeutic regimen for infertility, especially for patients receiving assisted fertility.